Macrozoobenthos Diversity in Mangrove Forest Waters of Tanjung Rejo Village Percut Sei Tuan Sub-Distrct, North Sumatra - Edi Azwar; Rani Miranda Sihombing; Muhammad Komarul Huda (Universitas Labuhanbatu, 2024)
This study aims to identify the species composition, abundance, and diversity of macrozoobenthos in the Waters of Mangrove Forest Dusun XIV Tanjung Rejo Village, Percut Sei Tuan Subdistrict, North Sumtra. Field survey methods and purposive sampling techniques were carried out by taking macrozoobenthos samples using standardized quadrats along randomly placed stations in the mangrove forest. The data obtained were then analyzed using the Shannon-Wiener diversity index, Simpson's dominance index. The results of research on the diversity of macrozoobenthos species obtained 17 species with 3 phyla, 3 classes, 8 orders, 16 families, and 16 genus. Measurement of physical and chemical factors of water obtained an average temperature of 28-31°C; average pH 7.2-7.6; average salinity 22-28°C; and the substrate is mud and silty sand. The type of macrozoobenthos that dominates in the area is Gastropoda. Macrozoobenthos diversity index value (H') 2.3905 at station I, 2.2567 at station II, and 2.1379 at station III, categorized as moderate. Based on these results, the Mangrove Forest Waters Area Dusun XIV Tanjung Rejo Village, Percut Sei Tuan Subdistrict is still within the threshold of good quality standards for the life of macrozoobenthos biota, which means that the environmental conditions are still not too polluted. This study makes an important contribution to the understanding of mangrove forest ecology and the importance of conservation and management of mangrove ecosystems as an integral part of the ecosystem